Host specialisation or generalism? Population genetics of the aphid Myzus persicae reveals dominance of superclones across diverse host plants - Nio, Yannis; Buchard, Christelle; Duval, Franck; Mahéo, Frédérique; Buzy, Ségolène; Le Ralec, Anne; Chesnais, Quentin; Mardoc, Gabin; Brault, Véronique; Candresse, Thierry; Malatesta, Ghislain; Monteiro, Amélie; et al. (Frontiers in Ecology and Evolution, 2025)
Most phytophagous insect species are specialized to feed on a narrow range of host plants, typically within the same genus or family, and sometimes even on a single plant species. However, some insect taxa are able to feed on plants from different families and are therefore considered to be generalists. Nevertheless, these generalist species can sometimes form cryptic species complexes or differentiate into host-based populations or races. Moreover, the host breadth of generalists is often measured under laboratory conditions, which may not accurately reflect the more challenging natural environments they encounter, and thus may lead to an overestimation of generalism. In this study, we used a population genetics approach to test whether Myzus persicae, a highly polyphagous aphid, is composed of host-specialized populations or clones, or whether generalism is an intrinsic characteristic of the species as a whole. We sampled M. persicae over four consecutive years in northern France from a variety of host plants belonging to different botanical families. We found that populations of M. persicae in northern France were predominantly composed of superclones, namely multilocus genotypes identified in many copies. In particular, four superclones dominated M. persicae populations, occurring in high proportions on a broad range of unrelated host plants in each year of the study. Moreover, the array of characterized genotypes of M. persicae formed distinct genetic clusters, but with no clear association to specific host plants. This study shows that under natural conditions and at the very fine genetic level of a single clone, the generalist characteristic of M. persicae holds. Thus, M. persicae remains an exceptional example of a true generalist species.